Mobilization of plant genetic resources from the territory of India - N. P. Loskutova; T. M. Ozerskaya (Труды по прикладной ботанике, генетике и селекции)
The article is dedicated to the mobilization of plant genetic resources from the territories of India to VIR’s collection by means of collecting explorations, germplasm requests and the exchange of accessions. The first, the longest and the only pre-war expedition to India was undertaken by Prof. V. V. Markovich; it lasted three years (1926–1928). He explored the Northern, North-Western (Punjab and Kashmir) and Southern India, where he collected 2557 germplasm samples. From 1956 through 1959, D. V. Ter-Avanesyan, who worked as an agricultural attaché at the USSR Embassy in India, familiarized himself in every detail with the country’s plant resources and agriculture, collecting more than 5000 samples. The late 1960s were marked by intensification of plant genetic resources introduction and new opportunities to organize regular collecting missions. In the period from 1969 to 1991, there were five plant exploration trips to India. In 1969, V. F. Dorofeev visited scientific institutions in 10 Indian states, got acquainted with the main trends in cereal crop breeding, and collected 938 plant samples. In 1975, V. N. Balabanov took part in a specialized collecting mission launched to study and collect wild forms of rice and to assimilate methods of breeding high-yielding, immune and highquality cultivars. In 1976, an expedition team led by V. L. Vitkovsky collected and studied wild and cultivated forms of fruit crops, subtropical plants and grapevines. The team visited 11 institutes and experiment stations in six states of India, and collected 725 accessions. In 1977, another collecting team led by R. A. Udachin, whose task was to study the system of nation-wide projects on crop improvement, traveled over five states, visited 24 scientific and academic institutions, and collected 3189 germplasm samples. The last collecting trip to India was led by S. G. Varadinov in 1983. The accent was made on groat crops, such as sorghum, pearl millet, etc. The team collected 250 varieties and local samples. In total, the Institute’s collecting and exploration activities in India mobilized and added to its collections over 13,146 accessions, representing 620 plant species. In addition to direct collecting in India, VIR has always been replenishing its holdings by seed requests. During the whole pre-war period, from 1925 through 1941, 2181 germplasm accessions were added. In the post-war times, acquisition of accessions by mail requests was performed within the framework of scientific collaboration and exchange via the Embassy of the USSR in India (agricultural attachés), the Ministry of Agriculture, and from 1985, the Agroindustrial Committee. All in all, from 1948 through 2018, 9278 accessions were introduced from India. The greatest number of accessions received by the Institute represented groat crops (over 3500), followed by wheat (1250), and industrial crops and grain legumes (nearly 1000 each). In total, during the whole period of its existence, the Institute has mobilized 24605 accessions.